Paradoxes and contradictions in health under the effect of global pressures: The case of the Portugal-Brazil-Africa geopolitical space - Carapinheiro, G. M. G. da S. (Interface: Comunicação, Saúde, Educação, 2019)
The Brazilian National Health System, known as SUS, is a social and development project in Brazil. For the first time, in 1988, the Brazilian Constitution recognised the right to health as a social right and a state duty (Article 196), via economic and social policies that were supposed to guarantee free, universal access. As Brazil is so much larger than Portugal, the decentralisation of SUS enabled municipal, state and federal-level management, in order to protect the country’s economic, social and health diversities. It is the municipalities, above all, that make the most important decisions on the management of people’s health. This brief description shows a health system that faces very complex, very different realities. But what I wanted to show you is that it is at the national level that Portugal and Brazil face governance and regulation challenges under the effects of supranational and transnational determinants.